Analisis penulisan assessment dan plan pada catatan perkembangan pasien terintegrasi (CPPT) pasien rawat inap kanker ovarium di RS X Kota Padang - Sugarman Putri, Pratiwi; Nasif , Hansen; Sari , Yelly Oktavia (Journal of Pharmaceutical and Sciences, 2023)
The documentation of patient condition progress performed by healthcare professionals through integrated care in patient medical records is known as Integrated Patient Progress Notes (IPPN), This research aims to assess the accuracy of pharmacists' IPPN writing for ovarian cancer patients at X Padang Hospital in October–November 2023. This research is a type of qualitatively descriptive case study. The data collection for this study is prospective. Data collection in this research is done in primary and secondary. Primary data collection is done by means of observation; secondary data acquisition is taken through medical records in the hospital. After conducting an analysis, it was determined that the results of the analysis plan of IPPNs for 36 patients were as follows: 0 CPPTs (0%) were accurately written, and all 36 IPPNs (100%) were written incorrectly. The analysis plan resulted in 36 IPPNs among the 36 patients. The accuracy rate for correctly identified IPPNs was 0% (0 IPPNs), while the rate for incorrectly identified IPPNs was 100% (36 IPPNs).